Answer:
h(x) =
![(1x)/(2) -(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aysgguuko83bgswmiv5z580lb5u0n78u2k.png)
Explanation:
Given : f(x)= 2x+1
To find : what is the inverse of the function .
Solution : We have given
f(x)= 2x+1
To find the inverse of the function :
Step 1: take y = f(x)
y = 2x + 1
Step 2: interchange the x and y
x = 2y +1.
Step 3: Solve for y
On subtracting both sides by 1
x -1 = 2y.
On dividing both sides by 2
y =
.
We can write
y=
![(1x)/(2) -(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aysgguuko83bgswmiv5z580lb5u0n78u2k.png)
Step 4 : take y = inverse of f(x) = h(x)
h(x) =
![(1x)/(2) -(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aysgguuko83bgswmiv5z580lb5u0n78u2k.png)
Therefore, h(x) =
![(1x)/(2) -(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aysgguuko83bgswmiv5z580lb5u0n78u2k.png)